Robert J.L. McClure (1807-1873) - Neatby, L.H. (ARCTIC, 1985)
Robert John LeMesurier McClure was born of Anglo-Irish gentry in 1807. He joined the Navy at the advanced age of 16 and for many years missed promotion. In 1836-1837 he was mate on George Back's Terror cruise in Hudson Bay and came back well initiated in the dangers of pack ice. . After years of obscurity, he was made first lieutenant of the Enterprise, in which James Ross was leading the first Franklin rescue expedition. McClure gained no credit on this almost abortive cruise, as ill health barred him from major sledge journeys, and when Ross was disabled, Second Lieutenant McClintock was given temporary charge of the ship. . On his return to England, McClure was made commander and appointed to the Investigator, which was to second Captain Richard Collinson of the Enterprise in a voyage by way of South America and Bering Strait to search the western Arctic. . Collinson had intended to reach the Arctic by making a wide sweep around the Aleutians; McClure now resolved to halve the distance by striking straight through the uncharted and fog-bound island chain. . By good fortune he carried with him two industrious diarists - his surgeon, Alexander Armstrong, and J.A. Miertsching, a Moravian missionary enlisted as Eskimo interpreter - as well as the gifted water-colour artist Lieutenant S.G. Cresswell. Confined near the shore by the pack and calling at Eskimo camps, McClure sailed past the Mackenzie River hundreds of miles to the east until at Cape Parry he was shouldered north by ice and made the lucky discovery of Prince of Wales Strait, separating Victoria and Banks islands and the last link in the passage sought. Ascending this almost to its outlet, he was caught by gale and tide and swept back to the narrows of the strait, where the ship was almost wrecked in the churning pack. When it froze solid, McClure took a sledge crew to its northern outlet on Parry's Viscount Melville Sound and linked their joint discoveries into one continuous Northwest Passage. In the spring, sledge parties mapped much of the shore of ...